2021
DOI: 10.1002/nafm.10614
|View full text |Cite
|
Sign up to set email alerts
|

Northern Madtom Use of Artificial Reefs in the St. Clair–Detroit River System

Abstract: The St. Clair and Detroit rivers historically supported abundant fish populations. However, like many river systems, these rivers have been greatly altered through the creation of navigation channels and other anthropogenic disturbances, resulting in the loss of fish and wildlife habitat and declines in native fish populations. To ameliorate this environmental degradation, artificial fish spawning reefs were constructed in the St. Clair and Detroit rivers. One native species to potentially benefit from artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Substantial recent work in the system has sought to increase the number of spawning reefs available for Lake Sturgeon and other species (e.g., Manny et al 2015;Hartig et al 2018;Fischer et al 2020). However, Johnson et al (2021) did not find a strong association between Northern Madtom and newly constructed reef INVESTIGATION OF ENDANGERED NORTHERN MADTOM habitat. Lamothe et al (2020) reported a negative relationship between Round Goby Neogobius melanostomus and Northern Madtom abundance in trawl data of the St. Clair River.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Substantial recent work in the system has sought to increase the number of spawning reefs available for Lake Sturgeon and other species (e.g., Manny et al 2015;Hartig et al 2018;Fischer et al 2020). However, Johnson et al (2021) did not find a strong association between Northern Madtom and newly constructed reef INVESTIGATION OF ENDANGERED NORTHERN MADTOM habitat. Lamothe et al (2020) reported a negative relationship between Round Goby Neogobius melanostomus and Northern Madtom abundance in trawl data of the St. Clair River.…”
Section: Discussioncontrasting
confidence: 60%
“…However, Johnson et al. (2021) did not find a strong association between Northern Madtom and newly constructed reef habitat. Lamothe et al.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations